Prevalence and Factors Associated with Pre-marital Sexual Intercourse Among Adolescents of School Age in Bima City - Silawati, Vivi; Silvana, Nana (Poltekita : Jurnal Ilmu Kesehatan, 2024)
Pre-marital sexual behavior among adolescents is still a concern in most of the countries, including Indonesia. The condition would be worse due to the discontinuation of the study, pre-marital pregnancy, and risk of sexually transmitted diseases. This study aimed to examine the prevalence of pre-marital sexual intercourse and factors associated among adolescents of school age in Kendal, Indonesia. This cross-sectional study employed 176 in grade XI from 9 classes in Senior High School 4 Bima, aged 15 to 18 years old in Bima City, Indonesia. The sample was selected by proportionate stratified random sampling. The dependent variable is pre-marital sex and the independent variables are knowledge, self-control, relationship status, role of teacher, and role of health worker. The data analysis was done using univariate (frequency and percentage) and bivariate analysis (Chi-square and simple logistic regression) using SPSS software. The result found prevalence of adolescents who were at risk of having sexual intercourse was 26.1%. The factors significantly associated with pre-marital sex are not having self-control (COR 8.5) and being in a relationship (COR 5.0). However, other variables including knowledge, the role of the teacher, and the role of health workers did not find significant association with pre-marital sex. Future studies can add more potential predictors to the study including the level of household, school, and community. The government needs to add the issue of pre-marital sex as well as the tendency to discontinue the study if pre-marital pregnancy occurs. Self-control can be strengthened by involving religious activity in school. Some recommendations for school-based sexual education programs, youth counseling services, or community interventions for the target population could work more to prevent pre-marital sexual intercourse among adolescents of school age.